Trends in biodiversity research over two decades: paradigmatic finders keepers? - France, Robert (Biodiversity: Research and Conservation, 2011)
Biodiversity research has been criticized for displaying the "founder effect" and not deviating in terms of study topic from the course set by its founding terrestrial ecologists more than three decades ago. I tested this hypothesis by examining over four thousand papers published between 1987 and 2008 in three international journals, Conservation Biology, Biological Conservation, and Biodiversity and Conservation. Analysis of temporal trends in types of organisms studied, types of ecosystems studied, types of methodologies used, and types of stresses investigated, revealed that there has been little movement away from the origins of the profession as being primarily concerned with the effects of forest habitat loss on charismatic terrestrial megafauna.